Selection criteria for building materials and components in line with the circular economy principles in the built environment: a review of current trends - Rahla, Mohamed Kamel (2021)
A growing concern is given to the environmental impacts caused by the construction industry. Waste generation, resource consumption, and greenhouse gas emissions are the main drawbacks of the rapid urbanization that the world is witnessing. As a response to these pressing issues, policymakers and academia are exploring the concept of Circular Economy (CE) to manage resources better and achieve resource efficiency while eliminating waste. One of the strategies to implement CE in the built environment is to select the appropriate building materials and components from the early stages to carry out the concept's principles along the value chain and create a closed-loop system. Therefore, this study aims at identifying selection criteria for building elements according to CE principles through a review of the latest research. Results have shown that little has been concretely achieved in terms of a paradigm shift to CE since the main focus of the literature is still the use of recycled products and the recyclability of building materials and components at their end-of-life. Although the present study is solely focused on the technical aspect of building materials and components, it outlines current adopted criteria to bring about a circular built environment and highlights the need for a more innovative approach to attain higher circularity levels.